G319(P) Headss up: should all adolescents be screened in the emergency department. (May 2019) - Begley, R; Roberts, Z; Mullen, S
Abstract : Adolescence is a time of dramatic transition and many problems faced are related to risk taking behaviour and psychosocial dysfunction. Despite time constraints and lack of clinical continuity characterised by emergency department (ED) visits, data shows that for some adolescents this may be their only point of care. The ED is therefore, well situated to identify risk-taking behaviour and perform psychological assessment. Methods: In our study we use the adolescent HEADSS screening tool to evaluate all adolescents (10–15 years) presenting to the ED. Post HEADSS interview, adolescents completed questionnaire asking: Where the questions relevant, simple to understand, better asked without carer present, if questions would put me off attending ED again and I would be happy being asked these questions if I attended with a breathing problem, injured arm or mental health problem. Following this a retrospective study of staff experience of using the screening tool was performed. The focus was on the feasibility of performing HEADSS screening on all adolescent presentations.I Results: Adolescents of all presentations (illness/injury/mental health) reported they would be happy to be asked the questions. It would not put them off attending in the future and would prefer to be asked questions with their carer out of the room. Adolescents identified with risk factors or areas of worry were referred to support services locally. Staff felt asking HEADSS added 5–10 min to the consultation; some 10–12 year olds seem too young to screen, and felt least confident about asking about mood and suicidal ideation. After this project staff feel we should ask only adolescents who present with at risk presentations which is our current practice. Conclusion: The ED has a role in screening adolescents to enable referral for supportive services. Our study showed adolescents would be happy to be asked screening questions with any type of presentation and it would stop them presenting again. Further work needs to be done on how the HEADSS screening tool is used, who does the assessment and the process of referral to support services and their availability and impact to justify use of this screening tool for all.